A review of the defrosting methods of air source heat pumps using heat exchanger with phase change material. (February 2019) - Shen, Jiubing; Qian, Zhaojun; Xing, Ziwen; Yu, Yue; Ge, Meicai
Abstract: Air source heat pumps (ASHPs) have been widely used for space heating in cold winter. When it operates in frosting environment, defrosting is necessary to maintain the system performance resulting in a discontinuous space heating. The defrosting time is an important parameter to evaluate the performance of different defrosting methods. At present, the widely applied ways for defrosting are the standard reverse-cycle defrosting and hot-gas bypass defrosting methods. For the two defrosting methods, the biggest problem is that no heat source is available for the defrosting cycle which leads to a long defrosting time. For the past few years, study on the use of heat exchangers with phase change material (PCM-HE) to storage heat for the defrosting receives lots interest. This paper presents a review of these reported defrosting methods using PCM-HE. The ASHPs with PCM-HE and their defrosting principles are introduced. Furthermore, the frequently-used phase change materials together with structure of PCM-HE are also summarized. Finally, the further research direction to realize effective defrosting and continuous heating of air-source heat pump products is discussed.